Data Mining Performance Assessment of Regional Development Planning Agency Employees Using Bayesian Classifier Algorithm - Nurfiah; Khairul Zaman (Jurnal Sistim Informasi dan Teknologi, 2023)
Performance is the success or work achievement of a person or group in an organization in completing work. Performance is the goals and targets given, performance appraisal is carried out. The results of employee performance consist of two, namely good or bad. These results are used as indicators in making decisions for giving rewards or punishments. This study aims to measure the level of employee performance with targets very good, good, quite good, less good and bad. The data used in this study is employee data. The assessment criteria are the results of the best employee assessment at the Regional Development Planning Agency in June 2022. The method used in determining employee performance is the Bayesian Classifier Algorithm. This algorithm uses the concept of classification. The data that is processed is first classified and followed by the analysis process in producing employee performance. This study uses training data as many as 43 records then the assessment is used as testing data. The results of the analysis of employee performance appraisal using the Bayesian Classifier Algorithm that the algorithm succeeded in classifying employee performance in accordance with the objectives of this study very well.